Modification of the existing maximum residue level for abamectin in bananas. (3rd October 2017) - ,; Brancato, Alba; Brocca, Daniela; De Lentdecker, Chloe; Erdos, Zoltan; Ferreira, Lucien; Greco, Luna; Janossy, Judit; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lythgo, Christopher; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Cheminova Agro Italia Srl submitted a request to the competent national authority in Italy to modify the existing maximum residue level (MRL) for the active substance abamectin in bananas. The data submitted in support of the request were found to be sufficient to derive MRL proposals for all crops under consideration. Adequate analytical methods for enforcement are available to control the residues of abamectin in the plant matrix under consideration. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of abamectin according to the reported agricultural practice is unlikely to present a risk to consumer health.